A demonstration of signalling involved in digital PABX / Ahmad Shukri Mohamed - Mohamed, Ahmad Shukri (2001)
This thesis highlights some basic guidelines of procedures as well as modelled signalling protocols used in modern private network digital telecommunication especially in Private Automatic Branch Exchange (PABX). This project is intended to demonstrate how a call connection is made using a telephone terminal through PABX (Inter-PABX) and Local Exchange. The demonstration was designed and developed by using a concept of electronic learning (e-learning). That means developing an interactive with fill multimedia contents.